August, Rebecca Beck (audio interview #1 of 3) - August, Rebecca Beck (b. 1/1/1883 - d. 08/ /1978); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - This first interview with Rebecca August took place in her room at the Jewish Home for the Aged in Boyle Heights. Because of the proximity to the freeway, the audio quality of the interview is only fair. Throughout the interview, August repeatedly returns to a discussion of her more recent activities, frequently referring to the honors and recognitions she received. TOPICS - family background; immigration to the US; experiences in shops in Chicago; Jane Addams; Hull House; involvement in strikes in New York; move to Seattle; organizing in Seattle; political beliefs; feminism;women's status; activities in the union; post-retirement life; and reactions to her activism; 1/29/1973